Soot temperature measurements and implications for time-resolved laser-induced incandescence (TIRE-LII) - Schraml, Stephan; Dankers, Stefan; Bader, Katharina; Will, Stefan; Leipertz, Alfred (Combustion and Flame, 2000)
Emission spectroscopy has been used to determine soot particle temperatures in an ethene diffusion flame both under normal combustion conditions and also after irradiation with an intense laser pulse. On the basis of these measurements, a check on the models and an improvement of parameters underlying time-resolved laser-induced incandescence (TIRE-LII) was performed. With this technique a two-dimensionally resolved measurement of soot primary particle sizes is feasible in a combustion process from the ratio of emission signals obtained at two delay times after a laser pulse, as the cooling behavior is characteristic of particle size. For accurate measurements, local gas temperatures must be known, which can be derived from the temperatures of the soot particles themselves. These have been measured by fitting full Planck curves to line-of-sight emission spectra after an inversion algorithm. The temperature and heat of vaporization of soot, which govern the energy and mass loss at high temperatures, were obtained by measurements of maximum particle temperature for various laser irradiances and a fit procedure to the theoretical dependence. Finally, the temperature decay of laser-heated soot was measured with high temporal resolution. Comparisons with model predictions show that soot temperatures are roughly 300 K higher than expected after the onset of vaporization, which indicates deficiencies in the present models of vaporization. It is demonstrated that the TIRE-LII performance is essentially unaffected by these shortcomings if LII signals are detected in a period where conductive heat transfer dominates and an appropriate correction is performed. (C) 2000 by The Combustion Institute.